2016
DOI: 10.1016/j.kint.2016.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities in biomarkers of mineral and bone metabolism in kidney donors

Abstract: Previous studies have suggested that kidney donors may have abnormalities of mineral and bone metabolism typically seen in chronic kidney disease. This may have important implications for the skeletal health of living kidney donors and for our understanding of the pathogenesis of long term mineral and bone disorders in chronic kidney disease. In this prospective study, 182 of 203 kidney donors and 173 of 201 paired normal controls had markers of mineral and bone metabolism measured before and at 6 and 36 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 32 publications
2
27
2
Order By: Relevance
“…The biochemical variations observed in this study after kidney donation are largely concordant with prior prospective reports 16,17,23,24 though most of these prior studies lacked comparator groups and investigated acute changes within the first week after surgery which our study did not. T 1 was selected as an optimal study timepoint to avoid acute postoperative changes (eg, within the first week) that could add to confounding and recalibration of mineral parameters was anticipated by T 1 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The biochemical variations observed in this study after kidney donation are largely concordant with prior prospective reports 16,17,23,24 though most of these prior studies lacked comparator groups and investigated acute changes within the first week after surgery which our study did not. T 1 was selected as an optimal study timepoint to avoid acute postoperative changes (eg, within the first week) that could add to confounding and recalibration of mineral parameters was anticipated by T 1 .…”
Section: Discussionsupporting
confidence: 91%
“…24 Given the small absolute differences in PTH documented, it is not surprising that the difference is not significant in our study. Simple sample size calculations to detect a true difference of 1pmol/L with 80% power would suggest a minimum of 222 matched pairs would be required.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…These changes include a decline in the serum concentration of 1, 25-dihydroxyvitamin D and phosphate, a decline in tubular phosphate reabsorption, and a rise in the concentration of serum PTH. 139,201,202,208 For example, one study showed that kidney donors had higher serum concentrations of fibroblast growth factor-23 and greater fractional excretion of inorganic phosphate compared with nondonor controls. 209 The Assessing Long Term Outcomes of Living Donation prospective cohort study found a 23% higher PTH concentration among 206 donors assessed at 6 months postdonation compared with concentrations among 198 healthy controls (52.7 vs 42.8 pg/mL, respectively) 201 that persisted at 36-month follow-up.…”
Section: Metabolic Bone Diseasementioning
confidence: 99%
“…The overall cardiovascular impact of the modest decline in whole-kidney GFR in an otherwise healthy adult is uncertain, but some prospective controlled studies have suggested that such alterations might have an effect on left ventricular mass even independent of blood pressure in otherwise healthy donors [ 18 , 19 ]. Other asymptomatic biochemical abnormalities, including elevations in fibroblast growth factor 23 and other biomarkers of mineral and bone metabolism, have also be observed [ 21 ].…”
Section: Introductionmentioning
confidence: 99%